381 views
3 votes
Rewrite each relation in the form y = a(x - h)^2 + k by completing the square

Rewrite each relation in the form y = a(x - h)^2 + k by completing the square-example-1
User Neetesh
by
6.0k points

2 Answers

4 votes

The
\( y = (x + 3)^2 - 10 \) is the quadratic equation in the desired form.

The
\( y = (x - 3)^2 - 13 \) is the quadratic equation in the desired form.

a)
\( y = x^2 + 6x - 1 \):

To rewrite this quadratic equation in the form
\(y = a(x - h)^2 + k\), we complete the square:


\[ y = x^2 + 6x - 1 \]

1. **Group the x-terms:**


\[ y = (x^2 + 6x) - 1 \]

2. **Complete the square (add and subtract
\((6/2)^2 = 9\)):**


\[ y = (x^2 + 6x + 9 - 9) - 1 \]

3. **Factor the perfect square trinomial and simplify:**


\[ y = (x + 3)^2 - 10 \]

So,
\( y = (x + 3)^2 - 10 \) is the quadratic equation in the desired form.

b.
\( y = x^2 - 6x - 4 \):

To rewrite this quadratic equation in the form
\(y = a(x - h)^2 + k\), we complete the square:


\[ y = x^2 - 6x - 4 \]

1. **Group the x-terms:**


\[ y = (x^2 - 6x) - 4 \]

2. **Complete the square (add and subtract
\((-6/2)^2 = 9\)):**


\[ y = (x^2 - 6x + 9 - 9) - 4 \]

3. **Factor the perfect square trinomial and simplify:**


\[ y = (x - 3)^2 - 13 \]

So,
\( y = (x - 3)^2 - 13 \) is the quadratic equation in the desired form.

User ELLIOTTCABLE
by
6.0k points
4 votes
Use:
(*)\ (a\pm b)^2=a^2\pm2ab+b^2

a)\\y=x^2+6x-1=\underbrace{x^2+2\cdot x\cdot3+3^2}_((*))-3^2-1=(x+3)^2-9-1=(x+3)^2-10



b)\\y=x^2-6x-4=\underbrace{x^2-2\cdot x\cdot3+3^2}_((*))-3^2-4=(x-3)^2-9-4=(x-3)^2-13
User Aaron Dufour
by
7.0k points